2022
DOI: 10.1002/lary.30154
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Model for Classification of Parotid Neoplasms Based on Multimodal Magnetic Resonance Image Sequences

Abstract: Objective: To design a deep learning model based on multimodal magnetic resonance image (MRI) sequences for automatic parotid neoplasm classification, and to improve the diagnostic decision-making in clinical settings.Methods: First, multimodal MRI sequences were collected from 266 patients with parotid neoplasms, and an artificial intelligence (AI)-based deep learning model was designed from scratch, combining the image classification network of Resnet and the Transformer network of Natural language processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…There is still a lack of uniform standards for the preoperative differential diagnosis between benign and malignant parotid tumors. Given the wide diversity of pathologic types of parotid tumors and similarity between their radiographic features, it is difficult to make an accurate diagnosis of benign and malignant parotid tumors based on radiographic features alone 3–5 . Clinicians must rely on their experience when making clinical judgment about parotid tumors, which usually results in a high level of subjectivity and uncertainty, and a greater possibility of misdiagnosis 9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is still a lack of uniform standards for the preoperative differential diagnosis between benign and malignant parotid tumors. Given the wide diversity of pathologic types of parotid tumors and similarity between their radiographic features, it is difficult to make an accurate diagnosis of benign and malignant parotid tumors based on radiographic features alone 3–5 . Clinicians must rely on their experience when making clinical judgment about parotid tumors, which usually results in a high level of subjectivity and uncertainty, and a greater possibility of misdiagnosis 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms offer a reliable statistical prognostic tool by incorporating a variety of risk factors for the differential diagnosis of tumors. 3,5 A visual predictive model can be built based on a nomogram for an individualized, accurate, and evidence-based risk estimate. Recently reported nomograms that have been built based on CT and ultrasound radiomics not only clearly diagnose the types of parotid tumors, but also effectively differentiate malignant from benign parotid tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In radiomics, the discrimination of SGTs have mostly reported results from T1WI, T2WI and DWI [ 18 , 19 , 20 , 21 ]. Only three machine learning study [ 58 , 59 , 60 ], using deep learning instead of radiomics, evaluated CE-T1WI images of the parotid gland. In agreement with our study, one of them found that CE-T1WI did not improve the classification of SGTs [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specialized DL algorithms have been developed to assist in differential diagnosis between benign and malignant parotid gland tumors in contrast-enhanced CT images [30], and ultrasonography [31]. MRI remains the gold standard in the diagnosis of salivary gland diseases, where DL models intend to automatically classify salivary gland tumors with very high accuracy [32,33].…”
Section: Head and Neck Imagingmentioning
confidence: 99%